Estudio de mejora para el área de producción de la empresa Filtros San Jorge SAC - Mendoza Cupe, Verónica Rocio (2016)
This thesis is the development of an enhancement plan in Filters San Jorge Company production area. The main objective is to raise and propose improvements in the production process of the company, especially in developing the production plan. Its purpose is to guide in making a correct plan through an integration process.